A Study on Environmental and Health History Risk Factors for Pneumonia Cases in Toddlers at Motui Health Center - Riana, Muslan; Rahmawati, Rahmawati; Amraeni, Yunita (Waluya The International Science of Health Journal, 2024)
Introduction: Pneumonia case data in North Konawe Regency / 1000 Toddlers in 2017 found 121 cases, in 2018 found 175 cases, in 2019 increased found 162 cases for 2020 decreased by 158 cases and in 2021 found increased with a total of 240 cases from 888 toddlers handled by health workers. The purpose of this study was to analyze the Risk Factors of Toddler Health History and Environment on Pneumonia Cases in Toddlers in the Motui Health Center Work Area. Method: The study used a quantitative method with an observational approach using a Case Control Study design. This study was conducted from March 1 to May 1, 2023. The sample size for each group was at least 46 samples. The comparison of case and control samples is 1: 1. The total sample is 92 respondents with a simple random sampling technique, using the SPSS 26 statistical test. Result: The health history of toddlers has a risk of 8.67 times for the occurrence of pneumonia, environmental conditions have a risk of 8.91 times for the occurrence of pneumonia in toddlers in the Motui Health Center Work Area. Conclusion: The need for a North Konawe District Health Service specifically for handling infectious disease programs.